High Serum Resistin Level may be an Indicator of the Severity of Coronary Disease in Acute Coronary Syndrome - Wang, Hao; Chen, De-you; Cao, Jian; He, Zuo-yun; Zhu, Bing-po; Long, Min (Chinese medical sciences journal, 2009)
Objective To investigate the correlation between serum resistin level, cardiovascular risk factors and severity of coronary disease in acute coronary syndrome （ACS）. Methods Alter evaluated by clinical history, electrocardiography, exercise tolerance tests, laboratory tests, and coronary angiography, 220 consecutive patients with suspected chest pain were divided into normal control group, stable angina pectoris （SAP） group, and ACS group, respectively. Baseline clinical characteristics, including height, weight, waist circumference, hip circumference, white blood cell count, high-sensitive C-reactive protein （hsCRP）, total cholesterol, triglyceride, low-density lipoprotein cholesterol and high-density lipoprotein cholesterol, were compared among three groups. ELISA was used to detect serum resistin levels. Pearson＇s correlation coefficient analysis was used to assess association between resistin and other traditional cardiovascular risk factors. Multinomial logistic regression analyses were used to define the relationship between serum resistin level and SAP or ACS. Results Serum resistin level in ACS group （1.18±0.48 μg/L） was significantly higher than that in normal control and SAP groups （0.49±0.40 and 0.66±0.40 μg/L; P〈0.01）. Only in ACS group, increased serum resistin level was significantly correlated with hsCRP （r=0.262, P=0.004） and white blood cell count （r=0.347, P=0.001）. Furthermore, serum resistin levels showed a stepwise increase with the number increase of 〉 50% stenosed coronary vessels. Multinomial logistic regression test demonstrated that serum resistin was a strong risk factor for ACS （OR=29.132, 95 % CI： 10.939-77.581, P〈0.001）. Conclusion These findings suggested the potential role of resistin in atherosclerosis and especially its involvement in ACS.